2018
DOI: 10.3390/cancers10080247
|View full text |Cite
|
Sign up to set email alerts
|

The Dynamic Roles of TGF-β Signalling in EBV-Associated Cancers

Abstract: The transforming growth factor-β (TGF-β) signalling pathway plays a critical role in carcinogenesis. It has a biphasic action by initially suppressing tumorigenesis but promoting tumour progression in the later stages of disease. Consequently, the functional outcome of TGF-β signalling is strongly context-dependent and is influenced by various factors including cell, tissue and cancer type. Disruption of this pathway can be caused by various means, including genetic and environmental factors. A number of human… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 179 publications
(207 reference statements)
2
19
0
Order By: Relevance
“…There has been increasing evidence supporting a primary role for TGFβ pathway activation in NPC [12,53,63,[65][66][67]. This current study demonstrated that miR-34c can be downregulated by TGFβ1, and that miR-449b overexpression can cause similar effects.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…There has been increasing evidence supporting a primary role for TGFβ pathway activation in NPC [12,53,63,[65][66][67]. This current study demonstrated that miR-34c can be downregulated by TGFβ1, and that miR-449b overexpression can cause similar effects.…”
Section: Discussionsupporting
confidence: 62%
“…We had previously demonstrated that miR-449b overexpression, another component of the validated prognostic DM signature [11], led to TGFBI mRNA degradation with subsequent TGFβ1 accumulation [12]. Given that TGFβ1 plays an important role in NPC progression [53,[63][64][65][66][67][68] and in the regulation of miRNAs, particularly miR-34a [52], we sought to measure TGFβ1 in these cell lines. Indeed, C666-1 cells (which have high miR-449b expression [12]) expressed higher levels of active TGFβ1 compared to either NP69 or NP460 cells (both of which have lower miR-449b expression [12]) ( Figure 1C).…”
Section: Mir-34c Is Downregulated By Tgfβ1mentioning
confidence: 99%
“…There has been increasing evidence supporting a primary role for TGFβ pathway activation in NPC [12,53,63,[65][66][67]. This current study demonstrated that miR-34c can be downregulated by TGFβ1, and that miR-449b overexpression can cause similar effects.…”
Section: Discussionsupporting
confidence: 61%
“…We had previously demonstrated that miR-449b overexpression, another component of the validated prognostic DM signature [11], led to TGFBI mRNA degradation with subsequent TGFβ1 accumulation [12]. Given that TGFβ1 plays an important role in NPC progression [53,[63][64][65][66][67][68] and in the regulation of miRNAs, particularly miR-34a [52], we sought to measure TGFβ1 in these cell lines. Indeed, C666-1 cells (which have high miR-449b expression [12]) expressed higher levels of active TGFβ1 compared to either NP69 or NP460 cells (both of which have lower miR-449b expression [12]) (Fig.…”
Section: Mir-34c Is Downregulated By Tgfβ1mentioning
confidence: 99%
“…Since EBV-positive NPC has a unique microenvironment rich in lymphocytes, its response to radiotherapy could differ significantly from other types of cancers. In addition, the EBV infection in cancer cells could further complicate the immune response in the tumor microenvironment [ 37 , 38 ]. Although the PD-1/PD-L1 axis is a potent inhibitor of immune activation, it has been suggested that PD-L1 expression might reflect the presence of antigen-induced anti-tumor immune pressure mediated by tumor-infiltrating lymphocytes [ 39 ].…”
Section: Discussionmentioning
confidence: 99%